THE HIGHLY PATHOGENIC INFLUENZA IN THE REPUBLIC OF BURYATIA AND PREVENTIVE MAINTENANCE IN EPIDEMIC SEASON 2009-2010 - S. S. Khankhareyev; G. S. Amagzayeva; L. A. Radnayeva (Acta Biomedica Scientifica, 2012)
The analysis of morbidity of the highly pathogenic influenza and acute respiratory viral infections in Republic of Buryatiya is lead. Data of laboratory monitoring behind circulation of pathogen agent of flue and the immunization of the population in preepidemic period are presented. Organizational and. practical actions on counteraction to flu A/H1N1/ are consecrated.